Permanent Perceptions, Unchanging Problems: Visual Arts Course in Primary School at the Context of Student-Teacher-Parent - Nurgül Çakmak; Burçin Türkcan (Anı Publishing, 2019)
The aim of this study is to examine the visual arts course in primary school in line with the opinions of students, teachers and parents. In the research, phenomenology research pattern was used in the framework of qualitative research approach. The study group consists of six students from fourth grade in the primary schools from the Gaziantep province and their tearchers and parents. The research data was collected from two sessions of semi-structured interviews. The collected data was analyzed and interpreted by the content analysis method. The following are the most remarkable results in all three groups of participants: The students think that they like this course because they can reflect their imagination freely, but that the course is limited to drawing; teachers see themselves as inadequate for this lesson, and parents do not have much expectation from their class teachers and children. The similarity of the results of this research with the results of other studies in this context indicates that different contexts and conditions do not reveal a significant difference. In this regard, it can be suggested to give particular importance to the family education related to the importance and necessity of art and art education together with in-service training that enrich both the perspectives and practices of teachers.